A high-strength film and preparation method thereof
By introducing functionalized graphene oxide nanosheets and silicate nanofibers into the PC film, the problem of insufficient strength of traditional PC films is solved, significantly improving the tensile strength and toughness of the film, and improving its applicability in special applications.
Patent Information
- Application Number
- CN202410917122.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-09
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-07-09
AI Technical Summary
Traditional PC films have shortcomings in strength, especially in special occasions where large external forces are required or high durability is required. The defect of insufficient strength limits its application range.
By introducing functionalized graphene oxide nanosheets and silicate nanofibers as reinforced fillers, the compatibility and binding force of graphene oxide with polycarbonate matrix is enhanced by grafting to form a high-strength film.
It significantly improves the tensile strength and toughness of the film, forms an effective enhancement network, prevents cracks from spreading, and improves the overall strength and processing performance of the film.
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of film processing, and more specifically, to a high-strength film and a preparation method thereof. Background Art
[0002] PC film, or polycarbonate film, is a film made of polycarbonate resin. With the continuous development of materials science and the increasing expansion of application fields, PC film has been widely used in electronic displays, automobile windows, building materials and other fields due to its excellent transparency, heat resistance, impact resistance and other characteristics. However, traditional PC film has obvious shortcomings in strength, especially in some special occasions that need to withstand large external forces or require high durability, such as aerospace, high-speed train windows, high-end smartphone screens, etc., its insufficient strength limits its application range.
[0003] In the related art, in order to improve the strength of PC film, researchers have tried various methods, such as adding inorganic fillers, changing the preparation process, etc. Although these methods have improved the strength of PC film to a certain extent, there are still some problems. For example, the addition of inorganic fillers may affect the transparency and toughness of PC film, while the change of preparation process may increase production costs, and the effect is not significant.
[0004] Therefore, it is urgent to develop a film with excellent strength performance so that the polycarbonate film material can be promoted and applied in some special occasions. Summary of the invention
[0005] In order to improve the defect of low film strength in the related art, the present application provides a high-strength film and a preparation method thereof.
[0006] The high-strength film provided in this application adopts the following technical solution:
[0007] A high-strength film, the raw materials of the film comprising:
[0008] 0.5-2 parts of functionalized graphene oxide nanosheets;
[0009] 1-3 parts of silicate nanofibers;
[0010] 400-600 parts of polycarbonate polyol;
[0011] Silane coupling agent 2-5 parts;
[0012] 30-50 parts of isocyanate crosslinking agent;
[0013] Chain extender 5-10 parts;
[0014] 3-5 parts of antioxidant;
[0015] 3-5 parts of lubricant.
[0016] By adopting the above technical scheme, functionalized graphene oxide nanosheets and silicate nanofibers are introduced as reinforcing fillers. Functionalized graphene oxide nanosheets have extremely high specific surface area and excellent mechanical properties. Functionalized graphene oxide nanosheets enhance the compatibility and bonding force with the polycarbonate matrix through bromine atom grafting. The introduction of bromine atoms can significantly improve the compatibility between graphene oxide and the polycarbonate matrix. This is because bromine atoms can act as a bridge to promote the interaction between GO and molecular chains through physical or chemical effects, reduce phase separation, thereby enhancing the interfacial bonding force of the composite material, effectively transferring the load, and improving the tensile strength and toughness of the film. In addition, the dispersibility of functionalized GO (especially GO grafted with bromine atoms) in the matrix will be significantly improved. This is because the presence of bromine atoms can reduce the interaction between GO sheets, making it easier to disperse evenly in the matrix, reducing agglomeration, and thus improving the overall performance and strength of the composite material. Good interfacial bonding and uniform dispersion enable functionalized GO to transfer loads more effectively in the composite material. When subjected to external forces, GO nanosheets can act as a reinforcing phase, effectively dispersing and bearing part of the load, thereby improving the tensile strength and toughness of the film.
[0017] There are three reasons why bromine atoms are grafted onto GO in this application. First, bromine atoms have specific chemical properties, such as high electronegativity and large atomic radius, which enable them to form stable chemical bonds on the GO surface while maintaining good compatibility with the matrix. In contrast, other organic functional groups may not be able to provide the same degree of interfacial bonding or compatibility. Second, GO grafted with bromine atoms may be easier to mix evenly with the matrix during processing and is not prone to phase separation. This is crucial for the preparation of high-performance films. Third, for high-strength films, the introduction of bromine atoms can optimize the overall performance of the composite material.
[0018] The high strength and toughness of silicate nanofibers play a reinforcing role similar to that of steel bars in the film, effectively preventing the expansion of cracks. Under the action of crosslinkers and chain extenders, the polymer chain structure of polycarbonate polyol forms a tighter and more ordered network, which enhances the cohesion of the material and ensures the basic performance and processability of the film. One end of the silane coupling agent molecule is combined with the inorganic reinforcing material, and the other end is compatible with the polymer matrix, which improves the interface bonding and promotes stress transfer. Isocyanate crosslinkers react with polymers to form a crosslinked structure, which improves the rigidity and strength of the material. Antioxidants protect the molecular structure of the material by capturing free radicals and inhibiting the occurrence of oxidation reactions. Lubricants reduce friction heat and internal stress during processing, making film molding more uniform.
[0019] In summary, the introduction of functionalized graphene oxide nanosheets and silicate nanofibers as reinforcing fillers significantly improves the mechanical strength of the film. Functionalized graphene oxide nanosheets enhance the compatibility and bonding with the polycarbonate matrix through bromine atom grafting, effectively transfer the load, and improve the tensile strength and toughness of the film. Silicate nanofibers, with their high aspect ratio and excellent mechanical properties, form an effective reinforcement network in the film, hinder crack propagation, and further improve the overall strength of the film. At the same time, polycarbonate polyol as a matrix material ensures the basic performance and processability of the film.
[0020] Optionally, the method for preparing the functionalized graphene oxide nanosheets comprises:
[0021] A1. Functional modification: disperse graphene oxide nanosheets in an organic solvent, add bromide, heat to 75-80°C, and then maintain the heating temperature for stirring and reacting for 1-2 hours;
[0022] A2. Separation and drying: The graphene oxide nanosheets after the functionalization reaction are subjected to solid-liquid separation, and the solid phase is washed with ethanol and then dried to obtain the functionalized graphene oxide nanosheets.
[0023] By adopting the above technical scheme, the preparation method of functionalized graphene oxide nanosheets of the present application ensures that the graphene oxide nanosheets can be effectively functionalized and modified, so that they can be better applied to thin films and significantly improve the strength and performance of the thin films. By dispersing the graphene oxide nanosheets in an organic solvent for functional modification, bromine atoms can be uniformly grafted on the surface of graphene oxide, increasing its compatibility and dispersibility with the polymer matrix, thereby improving the comprehensive performance of the film. In an organic solvent, the graphene oxide nanosheets can be fully dispersed, providing a good environment for the bromide to react with the functional groups on the surface of graphene oxide. Heating to 75-80°C and maintaining a stirring reaction for 1-2h can provide sufficient energy and time for the reaction to proceed fully, ensuring that the bromine atoms are effectively grafted to the surface of graphene oxide. The grafted bromine atoms change the surface chemical properties of graphene oxide, increase its compatibility with the matrix, and enable it to be better dispersed in the film to form a uniform reinforcement phase. In the subsequent separation and drying steps, unreacted substances and solvents are removed to obtain pure functionalized graphene oxide nanosheets, which provide high-quality reinforcement materials for the preparation of high-strength films.
[0024] Optionally, the bromide is any one of sodium bromide, potassium bromide and magnesium bromide.
[0025] By adopting the above technical scheme, sodium bromide, potassium bromide and magnesium bromide can provide bromide ions in the reaction system and react chemically with the functional groups on the surface of graphene oxide. These bromides have good solubility and reactivity, and can fully react with graphene oxide under given reaction conditions to achieve the grafting of bromine atoms. Different bromides behave similarly in the reaction, but may have a certain impact on the reaction rate and grafting effect due to differences in their physical and chemical properties. By selecting these specific bromides, the preparation process can be flexibly adjusted according to actual production needs and conditions to obtain the best functionalized graphene oxide nanosheets.
[0026] Optionally, the mass ratio of the graphene oxide nanosheets to the bromide is 1:(0.01-0.2).
[0027] By adopting the above technical solution, when the mass ratio is too small, that is, the amount of bromide is insufficient, the surface of the graphene oxide nanosheets cannot be fully grafted with bromine atoms, which may lead to poor compatibility with the matrix, easy agglomeration in the film, and inability to fully exert the reinforcing effect. On the contrary, when the mass ratio is too large, too much bromine atom grafting may change the structure and properties of graphene oxide, affect its reinforcing effect, and may even have an adverse effect on other properties of the film. By controlling the mass ratio within the range of 1: (0.01 - 0.2), the moderate functionalization of graphene oxide nanosheets can be achieved, so that it can achieve the best reinforcing effect in the film, and improve the strength and comprehensive performance of the film.
[0028] Optionally, the preparation method of the silicate nanofibers comprises:
[0029] B1. Preparation of a silicate precursor solution: mixing a silicate source with a solvent to form a silicate precursor solution;
[0030] B2. Fiber formation: injecting the silicate precursor solution into the spinneret of the spinning machine and applying a high voltage electric field to make the silicate precursor solution spray out from the spinneret to form nanofibers;
[0031] B3. Curing and heat treatment: The formed nanofibers are cured, then heated and cured at 40-60° C., and then heat treated at 1200-1400° C. to obtain silicate nanofibers.
[0032] By adopting the above technical scheme, when preparing the precursor solution, sufficient mixing allows the silicate source to be evenly dissolved in the solvent to form a uniform reaction system, laying the foundation for the subsequent formation of high-quality nanofibers. Under the action of a high-voltage electric field, when the solution is ejected from the spinneret, the droplets are stretched and refined by the electric field force, and nano-scale fibers are quickly formed. The curing treatment allows the fibers to be initially shaped and form a certain structure. During the heating and curing process at 40-60°C, the residual solvent and moisture are removed to further enhance the structural stability of the fibers. In the high-temperature heat treatment at 1200-1400°C, the crystal structure inside the fiber is optimized, defects are reduced, and the strength is significantly improved. These carefully prepared silicate nanofibers, after being incorporated into the film, can effectively bear and transmit stress, significantly improving the strength of the film.
[0033] Optionally, the average length of the silicate nanofibers is 100-500 nm.
[0034] By adopting the above technical solution, when the length of silicate nanofibers is too short, it is difficult for them to form a continuous reinforcement network in the film and cannot effectively transfer stress, thus affecting the strength improvement effect of the film. When the fiber length is too long, it is easy to entangle and agglomerate with each other during processing, resulting in uneven dispersion, which not only affects the reinforcement effect, but also may introduce defects and weaknesses in the film. Controlling the average length within the range of 100-500nm can make the silicate nanofibers evenly dispersed in the film, overlap each other to form an effective stress transfer path, improve the tensile and impact resistance of the film, and ensure the quality stability and consistency of the film.
[0035] Optionally, the chain extender is 1,6-hexanediol.
[0036] By adopting the above technical solution, during the reaction process, the hydroxyl groups at both ends of 1,6-hexanediol can react with the active functional groups on the polymer chain to connect the short-chain polymers to form longer molecular chains. As the molecular weight increases, the cohesion and strength of the polymer are improved. At the same time, the introduction of 1,6-hexanediol can also improve the crystallization properties and microstructure of the polymer, further optimizing the mechanical properties of the film. Due to its specific chemical properties and reactivity, 1,6-hexanediol can efficiently carry out chain extension reactions under given reaction conditions, providing a reliable guarantee for the preparation of high-strength films.
[0037] Optionally, the antioxidant is a 168-type phosphite antioxidant.
[0038] By adopting the above technical solution, during high-temperature processing and long-term use, the film is easily affected by factors such as oxygen and light and undergoes oxidation reactions, resulting in molecular chain breakage and performance degradation. The 168-type phosphite antioxidant can preferentially react with free radicals and convert them into stable products, thereby preventing free radicals from attacking molecules. At the same time, the antioxidant can also synergize with other auxiliary antioxidants to form a more powerful antioxidant system to fully protect the performance of the film. By effectively inhibiting oxidative degradation, the film can maintain good strength, transparency and other physical and chemical properties, extending its service life in various application scenarios.
[0039] The present application also provides a method for preparing a high-strength film, which adopts the following technical solution:
[0040] A method for preparing a high-strength film comprises the following steps:
[0041] S1, mixing polycarbonate polyol, silane coupling agent, isocyanate crosslinking agent and chain extender, heating to 80-120° C. to react and obtain a prepolymer;
[0042] S2, adding functionalized graphene oxide nanosheets and silicate nanofibers to the prepolymer, and continuing to heat and stir to form a mixture;
[0043] S3, adding the mixture into a twin-screw extruder, performing melt extrusion to obtain a film; and performing stretching treatment on the film to obtain a high-strength film.
[0044] By adopting the above technical scheme, the preparation method of the film provided by the application, through reasonable steps and process conditions control, can fully fuse each raw material and form an orderly structure, thereby successfully preparing a high-strength film. First, polycarbonate polyol, silane coupling agent, isocyanate crosslinking agent and chain extender are mixed and heated to react to obtain a prepolymer, which lays the foundation for subsequent processing. Then add functionalized graphene oxide nanosheets and silicate nanofibers, and make them evenly dispersed in the prepolymer by heating and stirring to form a mixture with excellent performance. Finally, melt extrusion and stretching treatment are carried out by a twin-screw extruder to obtain a high-strength film.
[0045] In summary, this application has the following beneficial effects:
[0046] 1. Significantly improve the mechanical strength of the film: By introducing functionalized graphene oxide nanosheets and silicate nanofibers as reinforcing fillers, the tensile strength and toughness of the film are significantly improved. Functionalized graphene oxide nanosheets are grafted with bromine atoms to enhance the compatibility and bonding with the polycarbonate matrix, effectively transferring the load, so that the film can better disperse and bear part of the load when subjected to external forces. At the same time, silicate nanofibers, with their high strength and high toughness, form a reinforcement network similar to steel bars in the film, effectively preventing the expansion of cracks and further improving the overall strength of the film.
[0047] 2. Optimize the interface bonding of composite materials: Bromine atoms on functionalized graphene oxide nanosheets act as bridges, promoting the interaction between graphene oxide and molecular chains through physical or chemical effects, reducing phase separation, and enhancing the interface bonding of composite materials. Silane coupling agents also further improve the interface bonding between inorganic reinforcement materials and polymer matrices, promote stress transfer, and enable composite materials to disperse loads more effectively when subjected to stress, thereby improving the overall performance of the material.
[0048] 3. Improve processing performance and finished product quality: Polycarbonate polyol as the matrix material ensures the basic performance and processability of the film. At the same time, antioxidants protect the molecular structure of the material and extend the service life of the material by capturing free radicals and inhibiting the occurrence of oxidation reactions. Lubricants reduce friction heat and internal stress during processing, making the film forming more uniform and improving the quality of the finished product. In addition, the uniform dispersion of functionalized graphene oxide nanosheets in the matrix reduces agglomeration and further improves the processing performance and finished product quality of the film. DETAILED DESCRIPTION
[0049] The present application is further described in detail below with reference to the embodiments. Example Example 1
[0050] Raw materials preparation:
[0051] Functionalized graphene oxide nanosheets: 1 kg of graphene oxide nanosheets were dispersed in 30 L of ethanol, 0.05 kg of sodium bromide was added, and the mixture was heated to 78° C. and stirred for reaction for 1.5 h. The mixture was then centrifuged and the solid phase was taken out and washed with ethanol and dried to obtain functionalized graphene oxide nanosheets.
[0052] Silicate nanofibers: Sodium silicate was used as the silicate source and mixed with deionized water at a volume ratio of 1:3 to prepare a precursor solution. The solution was injected into the spinneret of the spinning machine and an 18kV high voltage electric field was applied to form nanofibers. The nanofibers were first cured at room temperature for 10 hours, then heated at 50°C for 8 hours, and finally heat treated at 1300°C for 2 hours. The average length was 300nm.
[0053] A high-strength film, the raw materials comprising:
[0054] Functionalized Graphene Oxide Nanosheets 1kg
[0055] Silicate Nanofiber 2kg
[0056] Polycarbonate polyol 500kg
[0057] Silane coupling agent 3kg
[0058] Isocyanate crosslinking agent 40kg
[0059] Chain extender (1,6-hexanediol) 8kg
[0060] Antioxidant (168 type phosphite antioxidant) 4kg
[0061] Lubricant (dipentaerythritol stearate) 4kg
[0062] A high-strength film, the preparation method of which is:
[0063] S1: Mix polycarbonate polyol, silane coupling agent, isocyanate crosslinking agent and chain extender, and heat to 100° C. to react to obtain a prepolymer.
[0064] S2: adding functionalized graphene oxide nanosheets and silicate nanofibers to the prepolymer, and continuing to heat to 110° C. and stirring for 2 hours to form a mixture.
[0065] S3: adding the mixture into a twin-screw extruder for melt extrusion to obtain a film; and stretching the film to obtain a high-strength film. Example 2
[0066] Raw materials preparation:
[0067] Functionalized graphene oxide nanosheets: 1 kg of graphene oxide nanosheets were dispersed in 30 L of ethanol, 0.01 kg of potassium bromide was added, and the mixture was heated to 75° C. and stirred for reaction for 2 h, followed by centrifugation. The solid phase was taken, washed with ethanol, and dried to obtain functionalized graphene oxide nanosheets.
[0068] Silicate nanofibers: Sodium silicate was used as the silicate source and mixed with deionized water at a volume ratio of 1:4 to prepare a precursor solution. The solution was injected into the spinneret of the spinning machine and a 20kV high voltage electric field was applied to form nanofibers. The nanofibers were first cured at room temperature for 10 hours, then heated and cured at 40°C for 10 hours, and finally heat treated at 1200°C for 3 hours, with an average length of 100nm.
[0069] A high-strength film, the raw materials comprising:
[0070] Functionalized graphene oxide nanosheets 0.5kg
[0071] Silicate Nanofiber 1kg
[0072] Polycarbonate polyol 400kg
[0073] Silane coupling agent 2kg
[0074] Isocyanate crosslinking agent 30kg
[0075] Chain extender (1,6-hexanediol) 5kg
[0076] Antioxidant (168 type phosphite antioxidant) 3kg
[0077] Lubricant (dipentaerythritol stearate) 3kg
[0078] A high-strength film, the preparation method of which is:
[0079] S1: Mix polycarbonate polyol, silane coupling agent, isocyanate crosslinking agent and chain extender, and heat to 80° C. to react and obtain a prepolymer.
[0080] S2: adding functionalized graphene oxide nanosheets and silicate nanofibers to the prepolymer, and continuing to heat to 90° C. and stirring for 2.5 hours to form a mixture.
[0081] S3: adding the mixture into a twin-screw extruder for melt extrusion to obtain a film; and stretching the film to obtain a high-strength film. Example 3
[0082] Raw materials preparation:
[0083] Functionalized graphene oxide nanosheets: 1 kg of graphene oxide nanosheets were dispersed in 30 L of ethanol, 0.2 kg of magnesium bromide was added, and the mixture was heated to 80° C. and stirred for reaction for 1 hour, and then centrifuged. The solid phase was taken, washed with ethanol, and dried to obtain functionalized graphene oxide nanosheets.
[0084] Silicate nanofibers: Sodium silicate was used as the silicate source and mixed with deionized water at a volume ratio of 1:5 to prepare a precursor solution. The solution was injected into the spinneret of the spinning machine and a 20kV high voltage electric field was applied to form nanofibers. The nanofibers were first cured at room temperature for 12 hours, then heated and cured at 60°C for 6 hours, and finally heat treated at 1400°C for 1.5 hours, with an average length of 500nm.
[0085] A high-strength film, the raw materials comprising:
[0086] Functionalized graphene oxide nanosheets 0.5kg
[0087] Silicate Nanofiber 1kg
[0088] Polycarbonate polyol 400kg
[0089] Silane coupling agent 2kg
[0090] Isocyanate crosslinking agent 30kg
[0091] Chain extender (1,6-hexanediol) 5kg
[0092] Antioxidant (168 type phosphite antioxidant) 3kg
[0093] Lubricant (dipentaerythritol stearate) 3kg
[0094] A high-strength film, the preparation method of which is:
[0095] S1: Mix polycarbonate polyol, silane coupling agent, isocyanate crosslinking agent and chain extender, and heat to 80° C. to react and obtain a prepolymer.
[0096] S2: adding functionalized graphene oxide nanosheets and silicate nanofibers to the prepolymer, and continuing to heat to 90° C. and stirring for 2.5 hours to form a mixture.
[0097] S3: adding the mixture into a twin-screw extruder for melt extrusion to obtain a film; and stretching the film to obtain a high-strength film. Comparative Example
[0098] Comparative Example 1
[0099] A high-strength film, which differs from Example 3 in that an equal amount of non-functionalized graphene oxide nanosheets is used in the raw material to replace the functionalized graphene oxide nanosheets.
[0100] Comparative Example 2
[0101] A high-strength film, which is different from Example 3 in that silicate nanofibers are not added to the raw materials.
[0102] Comparative Example 3
[0103] A high-strength film, which is different from Example 3 in that no functionalized graphene oxide nanosheets are added to the raw materials.
[0104] Comparative Example 4
[0105] A high-strength film, which differs from Example 3 in that: the functionalized graphene oxide nanosheets in the raw material are obtained by grafting anhydride groups on the surface of graphene oxide, and when preparing the functionalized graphene oxide nanosheets, magnesium bromide is replaced by acetic anhydride in an equal amount, and the other operations remain unchanged.
[0106] Performance testing
[0107] The tensile strength of the films prepared by the methods described in the above embodiments and comparative examples was tested according to the requirements of the standard GB / T1040-2006, the tensile speed was 100 mm / min, each group of samples was tested independently 5 times, and the average value was taken as the tensile strength of the group of samples. The results are shown in Table 1.
[0108] Table 1 Test results
[0109] Experimental Group Tensile strength / MPa Example 1 85.5 Example 2 85.3 Example 3 85.8 Comparative Example 1 41.3 Comparative Example 2 56.5 Comparative Example 3 38.9 Comparative Example 4 46.2
[0110] Examples 1, 2, and 3 all used functionalized graphene oxide nanosheets, and their tensile strengths were significantly higher than those of Comparative Example 1 (using non-functionalized graphene oxide nanosheets) and Comparative Example 3 (without adding functionalized graphene oxide nanosheets). This indicates that the functionalized graphene oxide nanosheets significantly improved the tensile strength of the film by enhancing the interfacial bonding force with the polycarbonate matrix.
[0111] Although comparative example 4 also uses functionalized graphene oxide nanosheets, the functionalized groups are anhydride groups, and its tensile strength is lower than that of the example using sodium bromide functionalization. This may be because the graphene oxide functionalized with sodium bromide has better compatibility and stronger interface bonding force with the polycarbonate matrix.
[0112] Examples 1, 2, and 3 all added silicate nanofibers, and their tensile strengths were significantly higher than that of Comparative Example 2 (without silicate nanofibers). This indicates that the silicate nanofibers play a reinforcing role in the matrix and improve the tensile strength of the film. The introduction of silicate nanofibers may improve the mechanical properties of the film by increasing the mechanical support points of the material and hindering crack propagation.
[0113] By using functionalized graphene oxide nanosheets and silicate nanofibers as reinforcing fillers, the embodiments of the present application significantly improve the tensile strength of the film. This reinforcing effect is better than the case where unfunctionalized graphene oxide nanosheets are used alone or silicate nanofibers are not added. The specific functional groups (such as sodium bromide grafting) on the functionalized graphene oxide nanosheets enhance the interfacial bonding force with the polycarbonate matrix, allowing the nanofillers to be more effectively dispersed in the matrix, thereby improving the overall mechanical properties of the film. Additives such as silane coupling agents, isocyanate crosslinking agents, chain extenders, antioxidants and lubricants play a role in promoting prepolymerization, increasing molecular chain length, preventing oxidative degradation and improving processing performance during the preparation process, thereby indirectly improving the mechanical properties of the film.
[0114] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A high-strength film, characterized in that: The raw materials of the film include: 0.5-2 parts of functionalized graphene oxide nanosheets; 1-3 parts of silicate nanofibers; 400-600 parts of polycarbonate polyol; Silane coupling agent 2-5 parts; 30-50 parts of isocyanate crosslinking agent; Chain extender 5-10 parts; 3-5 parts of antioxidant; 3-5 parts of lubricant; The preparation method of the functionalized graphene oxide nanosheets comprises: A1. Functional modification: disperse graphene oxide nanosheets in an organic solvent, add bromide, heat to 75-80°C, and then maintain the heating temperature for stirring and reacting for 1-2 hours; A2, separation and drying: the graphene oxide nanosheets after the functionalization reaction are subjected to solid-liquid separation, the solid phase is washed with ethanol and then dried to obtain the functionalized graphene oxide nanosheets; The mass ratio of the graphene oxide nanosheets to the bromide is 1:(0.01-0.2).
2. A high-strength film according to claim 1, characterized in that: The bromide is any one of sodium bromide, potassium bromide and magnesium bromide.
3. A high-strength film according to claim 1, characterized in that: The preparation method of the silicate nanofibers comprises: B1. Preparation of a silicate precursor solution: mixing a silicate source with a solvent to form a silicate precursor solution; B2. Fiber formation: injecting the silicate precursor solution into the spinneret of the spinning machine and applying a high voltage electric field to make the silicate precursor solution spray out from the spinneret to form nanofibers; B3. Curing and heat treatment: The formed nanofibers are cured, then heated and cured at 40-60° C., and then heat treated at 1200-1400° C. to obtain silicate nanofibers.
4. A high-strength film according to claim 2, characterized in that: The average length of the silicate nanofibers is 100-500 nm.
5. The high-strength film according to claim 1, characterized in that: The chain extender is 1,6-hexanediol.
6. A high-strength film according to claim 1, characterized in that: The antioxidant is a 168-model phosphite antioxidant.
7. A method for preparing a thin film according to any one of claims 1 to 6, characterized in that: The steps include: S1, mixing polycarbonate polyol, silane coupling agent, isocyanate crosslinking agent and chain extender, heating to 80-120° C. to react and obtain a prepolymer; S2, adding functionalized graphene oxide nanosheets and silicate nanofibers to the prepolymer, and continuing to heat and stir to form a mixture; S3, adding the mixture into a twin-screw extruder, performing melt extrusion, and obtaining a film; The film is stretched to obtain a high-strength film.
Citation Information
Patent Citations
Preparation method and application of modified graphene oxide
CN110182795A
Metal-coated polyester film
CN113544200A